1979
DOI: 10.1002/1097-0142(197910)44:4<1256::aid-cncr2820440415>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The morphologic effects of radiation administered therapeutically for intracranial gliomas.A Postmortem study of 25 cases

Abstract: To investigate the pathologic consequences of therapeutic radiation, this morphologic study evaluated the brains of 25 patients with intracranial gliomas treated both with and without this form of therapy. Although beneficial effects such as the retardation of tumor growth were evident in these studies, among the seventeen patients who received from 5000--6000 rads for malignant gliomas, four developed "late delayed" radiation necrosis. The strong predilection of this tissue response for the white matter adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
0
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(90 citation statements)
references
References 65 publications
6
80
0
2
Order By: Relevance
“…Abnormal findings following ra diation therapy have been widely documented on MRI in children treated for brain tumors. 5,24 There is also evidence to suggest that standard or highdose chemo therapy can injure the normal brain, 9 and there appears to be a compounding effect when radiation therapy and che motherapy are used together. 3,14,15,17,20 In a Phase I/II study evaluating the use of carboplatin during radiation therapy in patients with medulloblastoma, the authors found 4 metastatic patients with early progression of leptome ningeal disease who were longterm survivors following palliative chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal findings following ra diation therapy have been widely documented on MRI in children treated for brain tumors. 5,24 There is also evidence to suggest that standard or highdose chemo therapy can injure the normal brain, 9 and there appears to be a compounding effect when radiation therapy and che motherapy are used together. 3,14,15,17,20 In a Phase I/II study evaluating the use of carboplatin during radiation therapy in patients with medulloblastoma, the authors found 4 metastatic patients with early progression of leptome ningeal disease who were longterm survivors following palliative chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Oligodendrocyte death can occur due to direct p53-dependent radiation apoptosis or due to exposure to radiation-induced tumor necrosis factor a (46, 47). Postradiation injury to the vasculature involves damage to the endothelium leading to platelet aggregation and thrombus formation, followed by abnormal endothelial proliferation and intraluminal collagen deposition (35,48). Further, hippocampal-dependent functions of learning, memory, and spatial information processing seem to be preferentially affected by radiation (49).…”
Section: Reducing Side Effects: Can Whole Brain Radiotherapy Be Omitted?mentioning
confidence: 99%
“…Studies with primate [9] and murine models [10], as well as human autopsy studies [11,12], have demonstrated that microvascular damage is a prominent pathologic component of radiation-induced brain injury, with endothelial degeneration leading to the formation cerebral microbleeds (CMBs). CMBs have also been observed in elderly patients without known underlying pathology [13,14], as well as in other degenerative central nervous system conditions, including cerebral amyloid angiopathy (CAA) associated with Alzheimer's disease and vascular cognitive impairment [11], where they have been linked to cognitive dysfunction [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%